2007
DOI: 10.1203/pdr.0b013e3181559774
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte mRNA Phenotype and Adverse Outcomes From Pediatric Multiple Organ Dysfunction Syndrome

Abstract: Impairment of the ability to mount an inflammatory response is associated with death from adult critical illness. This phenomenon, characterized by reduced monocyte production of proinflammatory mediators such as tumor necrosis factor ␣ (TNF-␣), is poorly understood in children. We hypothesized that differential expression of inflammation-related genes would be seen in monocytes from children with adverse outcomes from multiple organ dysfunction syndrome (MODS). Ex vivo lipopolysaccharide (LPS)-induced TNF-␣ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 45 publications
1
51
0
Order By: Relevance
“…It is proposed that the FMF mutations may affect binding of an unidentified inhibitory interaction partner, or affect the stability or localization of pyrin, and in this way it leads to a higher level of secreted IL-1β and intensified inflammatory responses, as observed in FMF patients. Pyrin appears to play an effective role in the regulation of the systemic inflammatory response, and the correlation of high levels of MEFV expression with adverse outcomes in critically ill children with multiple organ dysfunction syndrome confirms this association (32). …”
Section: Pyrin As a Mediator Of Il-1β Regulationmentioning
confidence: 69%
“…It is proposed that the FMF mutations may affect binding of an unidentified inhibitory interaction partner, or affect the stability or localization of pyrin, and in this way it leads to a higher level of secreted IL-1β and intensified inflammatory responses, as observed in FMF patients. Pyrin appears to play an effective role in the regulation of the systemic inflammatory response, and the correlation of high levels of MEFV expression with adverse outcomes in critically ill children with multiple organ dysfunction syndrome confirms this association (32). …”
Section: Pyrin As a Mediator Of Il-1β Regulationmentioning
confidence: 69%
“…These results suggest that preservation of the ability to mount a proinflammatory response may be an important determinant of survival. Our laboratory recently studied monocyte mRNA from 28 children with multiple organ dysfunction syndrome (MODS) [52]. We found that expression of mRNA coding for IL-10, IRAK-M, and pyrin (a putative inhibitor of intracellular inflammatory pathways) was elevated in nonsurvivors compared with survivors, with nonsurvivors demonstrating lower whole blood ex vivo LPS-induced TNFα responses.…”
Section: Mechanisms Of Immunoparalysismentioning
confidence: 99%
“…In fact, Ploder et al recently described a series of 19 polytrauma patients with sepsis in whom the degree of depression of the ex vivo TNFα response was more predictive of death on the day of sepsis onset than was the level of monocyte HLA-DR expression [64]. Our recent cohort of 28 children with MODS (25 of whom had septic shock) also underwent measurement of their whole blood ex vivo LPS-induced TNFα responses [52]. These data showed that nonsurvivors demonstrated lower ex vivo LPS-induced TNFα production over the first two weeks of MODS compared to survivors (Figure 4).…”
Section: Septic Diseasementioning
confidence: 99%
“…Quantitative PCR was done in the StepOne Plus machine using SYBR Green PCR mix (Applied Biosystems). The values of target genes were normalized to the values of two housekeeping genes, GAPDH and CAP-1, and expressed as relative copy number, as described previously (52)(53)(54).…”
Section: Real-time Pcrmentioning
confidence: 99%